Best Practice of Prevention of Covid-19 Transmission Through Small Island Region Quarantine - Zuardin Zuardin; Al Azhar; Wa Ode Heni Satriani (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2022)
This study aimed to analyze the quarantine strategy of Kadatua Island to prevent the transmission of Covid-19. The Data was obtained through direct observation and in-depth interviews with the Covid-19 countermeasure officer in the region. The research used an explanatory sequential mix-method, where the researcher first conducts quantitative research, analyzes the results, and arranges them, to explain in more detail with qualitative research. We found that Kadatua Island is a small island and separated from the mainland of South Buton district has the advantage that it is relatively easy to control the mobility of newly arrived residents from outside the area. Local governments and indigenous people work together in a regional quarantine effort with a coordinated supervision system. When the community wants to enter Kadatua Island, they will be directed to do a regional quarantine, empty houses will be prepared for 14-21 days and will be closely monitored by village officials. During the home quarantine, food for people undergoing quarantine was provided by their respective families and some were supplied from the village. In addition, the efforts of indigenous peoples are also called 'poago' by forbidding communities from doing activities outside and making sounds. All these efforts are considered effective, especially in controlling the transmission of Covid-19 on Kadatua Island. The effectiveness is supported by several geographical locations, local government policies that are health-oriented, and supports from citizens and indigenous peoples. Local governments need to make similar strategies on a larger scale for other island regions.